Children in Pornography after Sharpe - Benedet, Janine (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 2002)
In its recent decision in R. v. Sharpe, the majority of the Supreme Court of Canada upheld the Criminal Code provisions prohibiting the possession and making of child pornography, subject to two exceptions. Despite a narrow construction of the definition of child pornography and a broad reading of the statutory defences, the majority found that prohibiting individuals from making and possessing some kinds of child pornography was an unjustifiable limit on the freedom of expression guaranteed by s. 2(b) of the Canadian Charter of Rights and Freedoms. The dissent would have upheld the legislation in its entirety. This article argues that the majority of the Court erred in considering the value of freedom of expression in a detached and abstract manner. Operating in this abstract plane led the Court to approve two significant exceptions on the basis of hypothetical examples of overbreadth, without considering the reality of the exceptions as they relate to documented child pornography cases. As a result, the Court extended constitutional protection to some categories of material that are clearly harmful to children. This result should make us sceptical of the use in Charter cases of broad reading in remedies that create complex judicial amendments with unexamined consequences.